2023
DOI: 10.21203/rs.3.rs-2491164/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between gut microbiota and erectile dysfunction: a two-sample Mendelian randomization study

Abstract: Objective: Several observational studies have recently been reported to suggest an association between gut microbiotaand erectile dysfunction(ED). However, the causal relationship between gut microbiota and erectile dysfunction remains unclear. Therefore, the aim of this study was to clearly elaborate the causal relationship between gut microbes and erectile dysfunction. Methods: A two-sample Mendelian randomization study was conducted with summary statistics of the gut microbiota from the largest genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Wang et al (10) also reported a negative correlation, with their fully adjusted model indicating an OR of 0.97 (95% CI 0.95-0.99) and a 23% decrease in stroke incidence in the highest CDAI quartile versus the lowest (OR 0.77, 95% CI 0.64-0.92). Chen et al (11) found that each unit increase in CDAI reduced stroke risk by 3.4% (OR 0.966, 95% CI 0.937-0.997), collectively affirming the association between higher dietary antioxidant intake and reduced stroke risk. These findings collectively affirm the link between higher dietary antioxidant intake and reduced stroke risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Wang et al (10) also reported a negative correlation, with their fully adjusted model indicating an OR of 0.97 (95% CI 0.95-0.99) and a 23% decrease in stroke incidence in the highest CDAI quartile versus the lowest (OR 0.77, 95% CI 0.64-0.92). Chen et al (11) found that each unit increase in CDAI reduced stroke risk by 3.4% (OR 0.966, 95% CI 0.937-0.997), collectively affirming the association between higher dietary antioxidant intake and reduced stroke risk. These findings collectively affirm the link between higher dietary antioxidant intake and reduced stroke risk.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, a study by Hantikainen et al (9) which also used NEAC to assess dietary antioxidant intake, found no link between a highantioxidant diet and stroke risk. At the same time, a number of recent studies have further analyzed the association between CDAI and stroke by using CDAI as a measure of dietary antioxidant intake, and found that there is a nonlinear association between CDAI and stroke (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the increase in Actinomyces is often disclosed in infections with inflammation-related diseases 54 and can be causally related to accelerated age of biological senescence according to a recent study. 55 Eisenbergiella have also been recognized as a proinflammatory microorganism, manifested by the higher c-reactive protein, and increased release of inflammatory mediators from immune cells. 56,57 The opportunistic pathogenic bacteria, Peptoniphilus is often considered a major pathogen in various infections, especially chronic wounds such as diabetic foot ulcers and chronic compression, 58 and are associated with energy metabolism through the production of shortchain fatty acids (SCFAs) like butyrate.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Gut inflammation can result in systemic inflammation, which affects various parts of the body. Systemic inflammation has been linked to a range of chronic health conditions, including those related to spinal health [121].…”
Section: Intervertebral Disc (Ivd) Degeneration (Idd) and Gut Inflamm...mentioning
confidence: 99%
“…Lumbar spinal stenosis is a medical condition characterized by the narrowing of the spinal canal in the lower back, leading to a range of symptoms and discomfort. The burgeoning research in this field aims to shed light on how factors related to gut health might influence the development and progression of lumbar spinal stenosis [121,136].…”
Section: The Gut-ligament Axis: Exploring the Link To Lumbar Spinal S...mentioning
confidence: 99%